International marketing and the trading system (ITC GenevaCH, 2001)
Deals with marketing principles and key managerial decisions facing small- and medium-sized enterprises in developing and transition economies. Identifies and analyzes regulation problems in export markets. Includes case studies which illustrate in detail how business firms, in a variety of countries and industries are affected by regulatory change and how they respond to it.
Bibliography: p. 209-215